Analisis Efisiensi Belanja Sektor Publik Di Kabupaten/Kota Provinsi Sumatera Barat - Mailina, Septia; Satrianto, Alpon (Universitas Negeri Padang, 2025)
This study aims to measure the level of efficiency of public sector spending in the education, health and economic sectors. The data used is panel data, namely data from 19 districts / cities in West Sumatra Province in 2018-2022. The data used is secondary data obtained from the Central Bureau of Statistics and the Directorate General of Fiscal Balance. This research uses the Data Envelopment Analysis method. Efficiency measurement in this study uses the assumption of Variable Return to Scale with output-oriented. The results showed (1) there was 1 city that had achieved perfect efficiency, 11 regencies/cities achieved high efficiency and 7 districts/cities achieved medium efficiency in the education sector, (2) there were 2 cities that had achieved perfect efficiency, and 17 regencies /cities achieved high efficiency in the health sector and (3) there were no districts/cities that had achieved perfect efficiency, 12 regencies /cities achieved high efficiency and 7 regencies /cities achieved medium efficiency in the economic sector.